Reliability and optimization of structural systems : proceedings of Reliability and Optimization of Structural Systems, TUM, München, Germany, 7-10 April 2010 /: proceedings of Reliability and Optimization of Structural Systems, TUM, München, Germany, 7-10 April 2010. (©2010) - Unknown
No abstract available